2014
DOI: 10.1002/jmri.24663
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of chemotherapeutic response in bladder cancer using K-means clustering of dynamic contrast-enhanced (DCE)-MRI pharmacokinetic parameters

Abstract: Purpose To apply k-means clustering of two pharmacokinetic parameters derived from 3T DCE-MRI to predict chemotherapeutic response in bladder cancer at the mid-cycle time-point. Materials and Methods With the pre-determined number of 3 clusters, k-means clustering was performed on non-dimensionalized Amp and kep estimates of each bladder tumor. Three cluster volume fractions (VFs) were calculated for each tumor at baseline and mid-cycle. The changes of three cluster VFs from baseline to mid-cycle were correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
1
19
1
1
Order By: Relevance
“…Implementation of k-means clustering analysis: Previous studies on k-means clustering of MRI parameters showed that three clusters provided the best characterisation of cancer tissues [14, 17, 18]. Therefore, we selected k of 3 to perform k-means clustering of voxel-wise ADC values for each case.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of k-means clustering analysis: Previous studies on k-means clustering of MRI parameters showed that three clusters provided the best characterisation of cancer tissues [14, 17, 18]. Therefore, we selected k of 3 to perform k-means clustering of voxel-wise ADC values for each case.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we selected k of 3 to perform k-means clustering of voxel-wise ADC values for each case. The case-based k-means clustering was executed on Microsoft Excel using a method described in [17] to determined three cluster centres. Subsequently, two widely used measurements were calculated for each case: (1) mean intra-cluster distance (MICD), which is the average of the distance from each data point (ADC value) to its centre cluster; (2) the largest inter-cluster distance (LICD), which is the largest distance among three cluster centres: MICD=1Ni=13j=1Mifalse|xjcifalse|, where N is the total number of data points in the data set, i ranges from 1 to 3 and is denoted for cluster i , c i is the centre of cluster i , M i is the number of data points in cluster i , and x j is the j th data point of cluster i .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…head and neck malignancies. A recent article by Nguyen et al [75] used K-means cluster maps of DCE-MRI to show microvascular changes between responders and nonresponders to neoadjuvant chemotherapy. There has been no standardization of MP-MRI for bladder cancer across institutions either, thus, making comparison difficult.…”
Section: Assessing Treatment Responsementioning
confidence: 99%
“…DCE-MRI is a non-invasive method to assess microvasculature in a target tissue by monitoring the change of MR contrast over a certain period of time after injection. DCE-MRI has been utilized to diagnose malignant tumors and to assess tumor response to various therapies [1][2][3][4] . Quantitative DCE-MRI has presented high reproducibility 5 .…”
Section: Introductionmentioning
confidence: 99%